Settlement, economy and lifestyle: the changing social identities of the coastal settlements of West Norfolk, 450-1100 AD. - Davies, G.J. (2011)
The thesis explores social transformations in the settlement and economy of Anglo-Saxon England, between c.450 and 1100 AD, by using detailed case studies of rural settlement remains within a sub-region, coastal West Norfolk, to construct a systematic narrative of their development. The archaeological evidence for analysis is mainly composed of portable cultural material from rural settlements, combined with surveyed and excavated evidence of their morphology. Multiple and superimposed forms of evidence such as geophysical survey and fieldwalking survey are employed to analyse the diversity of rural settlements and the material expressions of social and economic change in this period and to challenge existing models.